Effects of ramipril on ventricular arrhythmia after myocardial infarction in rabbits - Zhong, Ya (Second Affiliated Hospital of Zhejiang University School of Medicine, 2014)
BACKGROUND: Ventricular arrhythmia (VA) is one of the most common complications of myocardial infarction (MI), and ventricular tachycardia and fibrillation are the main causes for sudden cardiac death. This study aimed to explore the effect of ramipril on the occurrence of VA and its mechanism after MI in rabbits. METHODS: Twenty-four New Zealand rabbits purchased from the Wuhan Laboratory Animal Research Center were divided into three groups: sham-operated (SHAM) group (n=8), MI group (n=8) and MI with ramipril (RAM) group (n=8). Rabbits in the SHAM group received a median sternotomy without ligation of the left ventricular coronary artery. Rabbits in the MI and RAM groups received a median sternotomy followed by ligation of the left coronary artery. The successful anterior MI was confirmed by elevation of the ST segment with more than 0.2 mV in lead II and III. After MI, rabbits in the RAM group were fed with intragastric ramipril (1 mg/kg per day) for 12 weeks. Before and 12 weeks after MI in the three groups, ventricular tachycardia or fibrillation (VT/VF) episodes and MAP in cadiocytes of the epicardium, mid-myocardium and endocardium were recorded by a multichannel physiograph. Student's t test and ANOVA were used for statistical analysis. RESULTS: VT/VF episodes were decreased more markedly in the RAM group than in the MI group after 12 weeks (2.6±0.8 vs. 12.4±2.9, P<0.05). Twelve weeks after MI, the duration of repolarization for 90% (APD(90)) of three-tier ventricular myocytes in the MI group was longer than that before MI (258.2±21.1 vs. 230.1±23.2, 278.0±23.8 vs. 245.8±25.4, 242.6±22.7 vs. 227.0±21.7, P<0.05). However, the APD(90) was not significantly different at 12 weeks before and after MI in the RAM group (P>0.05). Moreover, the transmural dispersion of repolarization (TDR) was increased more markedly 12 weeks after MI in the MI group than in the SHAM and RAM groups (36.2±10.2 vs. 18.7±6.2, 24.9±8.7, P<0.05). But the TDR was not significantly different between the RAM and SHAM groups (18.7±6.2 vs. 24.9±8.7, P>0.05). CONCLUSION: Ramipril may reduce the incidence of malignant ventricular arrhythmia via improvement of transmembrance repolarization heterogeneity after MI.